Teaching Writing Recount Text by Using Cooperative Learning Type Team Assisted Individualization (TAI) Strategy - Muhammad Usman; Novi Yani; Liza Malvina Ubat (English LAnguage Study and TEaching, 2021)
The objective of this study is to find out if there is a significant difference between the eighth-grade students of SMP Islam YPUI Banda Aceh who are taught writing recount text by using TAI strategy and those who are taught without using TAI strategy. This study was conducted by using quantitative approach and research design used was experimental study. The population of this study was all eight grade students of SMP Islam YPUI Banda Aceh. The total population is 60 students who are composed of two classes; VIII Male and VIII Female. Every class consisted of 30 students.While the samples of this study were the students who were taken from both classes. One class was as an experimental group and the other was as the control group. In this study, class VIII Female  was taken as control group and class VIII Male  was taken as experimental group.The data was  analyzed by using t- test. Based on the result of the study, the writer found that there was a significant difference between the two groups. It can be proven from the result of this study where the result of post-test of the both group was 4.26, it was greater than t-table (2.00).Based on the result of the study, English teachers of SMP Islam YPUI Banda Aceh who teach writing skill especially recount texts are suggested to use TAI strategy in teaching and learning process because it can improve the students’ ability in mastering writing especially writing recount  text.